1981
DOI: 10.1017/s0021859600040818
|View full text |Cite
|
Sign up to set email alerts
|

Field studies on leaching behaviour of a highly saline-sodic soil under two modes of water application in the presence of crops

Abstract: The leaching behaviour of a highly saline-sodic, moderately permeable, sandy-loam soil was evaluated under continuous and intermittent submergence conditions in a longterm field study in the presence of rice and subsequent wheat and sesbania crops. Leaching curves with respect to both desalinization and desodification showed that leaching efficiency was considerably higher with intermittent than with continuous submergence. The curves were useful in determining the amount of leaching water needed for a given m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…This indicates that a piston-like displacement of soil solution occurred in these plots. This behaviour has also been recorded by Smiles et al (1978Smiles et al ( ,1981, Dahiya, Singh, Richter & Singh (1984) and many others in laboratory columns, Dahiya et al (1981Dahiya et al ( , 1982 in 2 x 2 m cropped plots, and by Leffelaar & Sharma (1977), Khosla et al (1979) and Dahiya et al (1983) in small infiltrometers.…”
Section: Nature Of Displacement Of Saline Constituentssupporting
confidence: 64%
See 3 more Smart Citations
“…This indicates that a piston-like displacement of soil solution occurred in these plots. This behaviour has also been recorded by Smiles et al (1978Smiles et al ( ,1981, Dahiya, Singh, Richter & Singh (1984) and many others in laboratory columns, Dahiya et al (1981Dahiya et al ( , 1982 in 2 x 2 m cropped plots, and by Leffelaar & Sharma (1977), Khosla et al (1979) and Dahiya et al (1983) in small infiltrometers.…”
Section: Nature Of Displacement Of Saline Constituentssupporting
confidence: 64%
“…Similar results were also obtained for bare fields of such soils in Iraq (Dieleman, 1963), Peru (Van Alphen, 1975) arid in this part of India (Leffelaar& Sharma, 1977;Khosla, Gupta & Abrol, 1979). Dahiya et al (1981Dahiya et al ( , 1982 obtained similar results for the experimental soil in cropped plots. Figure 3 further shows that in 2 x 2 m plots (S,) under IP, ESP reduction in the soil profile at 1 pore volume was (1-0-225) 100 = 77-5%.…”
Section: Nature Of Displacement Of Saline Constituentssupporting
confidence: 57%
See 2 more Smart Citations
“…Such a strategy should result in more efficient use of water for leaching. Several experiments have shown that leaching efficiency is, in fact, increased under intermittent flow (Oster et al, 1972;Dahiya et al, 1981;Meiri & Plaut, 1985). Miller et al (1965) observed chloride displacement in Panoche clay loam and found that intermittent ponding of the soil with 5-cm increments of water was 1.8 times more efficient in leaching the applied chloride from the profile than a single ponding with the same volume of water, and so less water was needed.…”
Section: Introductionmentioning
confidence: 99%